Failing Gracefully: A Reflection on Scholarship Engagement in Engineering - Felicia Green (Journal of Scholarly Engagement)
The reasons women engineers decide to resign the engineering field has been a significant focus in the current STEM literature due to high turnover rates of qualified women engineers from the profession (Fouad, Chang, Wan, & Singh, 2017; Singh, Zhang, Wan, & Fouad, 2018). While there is a significant number of women engineers that leave the profession due to the work environment and organizational structure of the engineering field, there are some that remain despite the adversity (Fouad et al., 2017; Singh et al., 2018). The purpose of this article is to provide insights into the elements that constructed my decision-making process, which resulted in a decision to persist working in engineering. In following John Dewey’s critical reflection process, elements of my decision-making process considered the effect of stress on decision-making, the influence of identity development, and the influence of scholarly engagement on my persistence and final decision to remain in the engineering industry. As a result, the management of my physiological stress responses allowed for engagement in these scholarly activities in and outside of my school work. Furthermore, the engagement in scholarly activities are suggested to have strongly influenced the enrichment of established engineering identities.